Sexual assault and sexual harassment at the US military service academies. Issue 3 (4th May 2018) - Rosenstein, Judith E.; Angelis, Karin De; McCone, Dave R.; Carroll, Marjorie H.
ABSTRACT: As hybrids of civilian colleges and the military, the United States military service academies provide a unique lens through which to examine sexual harassment and assault. They are also lightning rods for scrutiny and criticism, and testing grounds for innovation, intervention, and change. In this article, the authors provide an introduction to the academies and consider cultural and contextual factors, including masculinity and tokenism, that may influence student attitudes and experiences regarding these issues. In addition, they examine reports spanning almost a decade that show how rates of sexual harassment and assault have changed and make comparisons to both the broader military and civilian colleges and universities when possible. Finally, the authors discuss relevant prevention and response efforts at each institution, address implications, and suggest ways forward.